ECONOMIC VALUATION OF MANGROVE ECOSYSTEM IN UJUNG LOE DISTRICT BULUKUMBA REGENCY - Sri Mardiyati; Maghfira Ihdayatul; Syafiuddin; Abdul Haris; Amruddin (Syarif Hidayatullah State Islamic University Jakarta, 2025)
This study aims to analyze the potential utilization and economic valuation of mangrove forest ecosystems. This study was conducted in Manyampa Village, Ujung Loe District, Bulukumba Regency, South Sulawesi Province. Samples were selected using a purposive sampling method, involving 20 pond fish farmers, 20 crab catchers, and 20 tourists. The study employed both descriptive quantitative and qualitative data analysis methods. This study indicates that the mangrove forest in Manyampa Village covers 27 hectares; however, only 7 hectares are currently utilized. Direct benefits such as mangrove fruits, wood products, and protective functions against abrasion, storm surges, and saltwater intrusion. Indirect benefits such as fish-shrimp-crab habitat, nutrient sources, environmental education, and ecotourism. The direct benefit value of the economic valuation of the mangrove ecosystem is IDR 4,562,963,185.00 per hectare per year. The indirect benefit value from milkfish (bandeng) cultivation in ponds is estimated at IDR 741,925,000.00 per hectare per year, and the value of coastal fishermen's catch is IDR 11,910,000.00 per hectare per year. The economic value of ecotourism in the mangrove forest ecosystem is estimated at IDR 89,250,000 per hectare per year. The mangrove forest ecosystem in Manyampa Village has an estimated economic value of IDR 5,406,048,185 per hectare per year. Given the total area of 27 hectares, the overall annual economic value of the mangrove forest is approximately IDR 145,963,300,995.